2022
DOI: 10.1002/agj2.21045
|View full text |Cite
|
Sign up to set email alerts
|

Rapid change in soil properties after converting grasslands to crop production

Abstract: Changes to land management over the last 150 years, primarily the conversion of perennial grasslands to agricultural production dominated by annual row crops, have greatly changed soil properties and reduced the soil's ability to infiltrate and store water in the soil profile. Direct near-term response at the time of conversion of an uncultivated remnant prairie to row crops is rare, especially responses that include repeated measurements on the same parcel of land and resampling of soils to a depth of 1 m to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Multiple studies have confirmed that soils under natural vegetation cover exhibit decreasing levels of soil organic matter after cultivation [69]. Carbon loss from such soils has been estimated to range between 30% and 50% after converting grasslands into agricultural lands [70,71]. Wastelands and bare lands, which remain in their natural state for extended periods, lack surface vegetation and possess inadequate water and nutrient retention abilities.…”
Section: Characteristics Of Soil Properties Under Different Land Usesmentioning
confidence: 99%
“…Multiple studies have confirmed that soils under natural vegetation cover exhibit decreasing levels of soil organic matter after cultivation [69]. Carbon loss from such soils has been estimated to range between 30% and 50% after converting grasslands into agricultural lands [70,71]. Wastelands and bare lands, which remain in their natural state for extended periods, lack surface vegetation and possess inadequate water and nutrient retention abilities.…”
Section: Characteristics Of Soil Properties Under Different Land Usesmentioning
confidence: 99%
“…Additionally, certain practices (e.g. tillage) involved in some land use conversions or land use intensification, can rapidly change soil properties, with declines in soil organic carbon observed after only two years following conversions of prairie grasslands to croplands [51]. To gain a more in-depth understanding of the functional changes occurring after land use conversion, larger-scale studies are required that allow for multiple comparisons between converted sites and their former and current land uses, and at sufficient scale to account for the huge natural spatial variations in bacterial community traits.…”
Section: Introductionmentioning
confidence: 99%
“…The natural ecosystems in the US Great Plains were fully functional under the native prairie vegetation (DeLuca & Zabinski, 2011; Ford & McPherson, 1996). In the past century, the conversion of grasslands to croplands and intensive tillage for farming has resulted in massive depletion in soil organic matter (SOM) storage (Lal, 2002, 2004; Strock et al., 2022). With the conversion to croplands, agroecosystems have depleted SOM storage by 54%–63% (Ghimire & Khanal, 2020; Ghimire et al., 2015).…”
Section: Introductionmentioning
confidence: 99%